A quasi-static model for kinematic analysis of a feed driving mechanism. (June 2020) - Guo, Shudong; Wang, Gang; Qi, Zhaohui; Zhuo, Yingpeng; Wu, Zhigang
Highlights: A quasi-static model for kinematic analysis of the rope-pulley system is proposed. Axial mobility characteristic of the rope is considered. The slip of the rope on the winch is considered when it is not wrapped closely. The exact position is got if the axial speed matches winch's rotational velocity. Abstract: A quasi-static model is proposed for kinematic analysis of the feed driving mechanism designed for China's Chang'e Lunar Exploration Program, which is a type of rope-pulley system used to provide driving force for drilling and sampling of lunar soil. This model does not take into account the inertia force acting on the rope because the mechanism is operated in a relatively enclosed device and the drilling speed is low. First, an appropriate method for spatial description of the rope-pulley system is applied on the basis of the model. Next, variables for kinematic description of the rope-pulley system are determined. Some key spatial points on the rope in contact with two pulleys, the winch, and the drilling rig are formulated. Then, the slip phenomenon occurs at the output terminal of the rope on the winch when the rope is not wrapped closely is analyzed. The results from numerical examples show that the rope tension and the driving moment vary depending on the way the rope is wrapped around the winch and the driving velocity.